OPTIMIZING DISTRIBUTION ROUTE OF PACKED DRINKING WATER WITH THE CLARKE AND WRIGHT SAVINGS AND NEAREST NEIGHBOR METHODS (Case Study of PT. GSI) - Dwi Agustina Kurniawati; Rian Puji Kusuma; Dwi Kristanto; Noordin Mohd. Yusof; Kuan Yew Wong (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2021)
In the business, distribution has a very important role. The distribution process must be able to deliver products on time while it also reduces the transportation costs which can consume around 50% of the company's total logistics costs. If distribution costs can be reduced, it can indirectly increase the company’s profit. PT. GSI, located in Yogyakarta, is a distributor of packed drinking water company with brand “PLG”. In determining the distribution route, PT. GSI does not use any scientific method and only uses the driver’s intuition. The purpose of this study is to optimize the distribution route of the “PLG” packed drinking water delivery to obtain the minimum mileage by using the Clarke and Wright Savings and Nearest Neighbor methods. The Clarke and Wright Savings method and the Nearest Neighbor method are used because the customer locations are far from each other and there are also customers whose delivery locations are centered on one delivery area, so that the calculation of distance savings is needed. Then the evaluation is done to determine which method is better. The comparison of the solution for data on 1st ,2nd ,3rd ,4th, and 6th March 2021 showed that the Nearest Neighbor method proposed best solution while data on 5th March 2021 showed that Clarke and Wright Savings giving the best solution. The results show that the Nearest Neighbor method provides better result in determining the distribution routes of PT. GSI.